The nominal machine - Cimatti, Felice (Rivista Italiana di Filosofia del Linguaggio, 2024)
The problem with the very notion of “hate speech” is that it seems possible - at least in principle - to imagine a linguistic scenario in which such violent use of languagecould be eliminated by actual communication. In fact, such a scenario is completely unrealistic, because at the core of every act of naming lies an ineliminable violent power, the power to assign an indeterminate entity a stable and determinate position in the world ruled by language. In this paper, such an unsurpassable hate character of every linguistic act is discussed through an analysis of Herman Usener’s theory of “momentary gods” and Franz Kafka’s story In the penal colony.